INVENTARISASI TUMBUHAN BERKHASIAT ANTIINFLAMASI DI HUTAN KOTA PEKANBARU - Zulingga Putri, Dinda; Wan Syafii; Darmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inflammation is a biological response of the body to infection and tissue damage that may trigger various health disorders, including respiratory system disorders. Medicinal plants are known to contain secondary metabolites such as flavonoids, alkaloids, tannins, and saponins that function as natural anti-inflammatory agents. Pekanbaru Urban Forest possesses a high diversity of plants potentially utilized as traditional medicinal resources; however, information regarding anti-inflammatory plants in this area remains limited. This study aimed to inventory anti-inflammatory plants found in Pekanbaru Urban Forest. The research was conducted from December 2025 to April 2026 using a descriptive exploratory method through field exploration techniques. Plant identification was carried out based on morphological characteristics and supported by literature studies related to bioactive compounds and anti-inflammatory activities. The results showed that 16 plant species belonging to 10 families, and 8 orders possessed anti-inflammatory properties. These plants contain bioactive compounds such as flavonoids, alkaloids, tannins, and saponins which play roles in inhibiting inflammatory processes. The most dominant families found were Myrtaceae and Fabaceae. The findings indicate that Pekanbaru Urban Forest has potential as a source of anti-inflammatory medicinal plants that can support herbal research development and biodiversity conservation.